Human Brucellosis: Incidence, Diagnosis, and Clinical Characteristics of Patients Admitted in a Tertiary Care Setting of Pakistan - Irshad, Memoona; Aziz, Abdul; Jamil, Bushra (Infectious Diseases Journal of Pakistan, 2022)
Background: Brucellosis is a known widespread zoonotic disease. Humans may be infected with Brucella species either due to direct contact with infected animals or ingesting natural products of animal origin. Brucellosis is included in one of the neglected zoonotic diseases, and as per World Health Organization (WHO), almost 500,000 cases are reported every year. The endemicity of this disease in developing countries is likely due to ineffectivedisease control programs. Study design: It is a retrospective observational study from the 1988 to 2019. Results: The study showed the highest incidence of disease was in year 2016 with male to female ratio of 2.1:1. Species identified were B. abortus, B. melitensis with positive serological titers of more than or equal to 1:80 or positive blood cultures. Most common symptom in patients was fever. Conclusion:The study focuses in establishing the importance of animal contact history in patients with pyrexia of unknown origin (PUO). Brucellosis is one of the important differentials to be included in list of PUO. Key words: Human brucellosis, Brucella, Brucella species, Pakistan